Electrodes: Flexible Supercapacitors Based on Bacterial Cellulose Paper Electrodes (Adv. Energy Mater. 10/2014). Issue 10 (July 2014) - Li, Shaohui; Huang, Dekang; Zhang, Bingyan; Xu, Xiaobao; Wang, Mingkui; Yang, Guang; Shen, Yan
<x xml:space="preserve">Abstract</x> In article number 1301655, Mingkui Wang, Guang Yang, Yan Shen, and co‐workers describe a simple and convenient method for fabricating freestanding and flexible paper electrodes based on bacterial cellulose, multiwalled carbon nanotubes, and a polyaniline composite. The hybrid paper exhibits impressive electrochemical performance and is a promising candidate as a new electrode material for assembling a lightweight and low‐cost energy storage device as the power for stretchable/flexible electronic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>